Psychological and behavioral response on the COVID-19 pandemic in individuals with bipolar disorder: A multicenter study. (April 2022) - Dalkner, Nina; Ratzenhofer, Michaela; Fleischmann, Eva; Fellendorf, Frederike T.; Bengesser, Susanne; Birner, Armin; Maget, Alexander; Großschädl, Katja; Lenger, Melanie; Platzer, Martina; Queissner, Robert; Schönthaler, Elena; et al.
Highlights: People with BD had more depression and somatization than HC during the pandemic. Distress due to social distancing was related to all clinical symptoms in BD. COVID-19 fears were related to more anxiety and worse sleep quality in BD. Individuals with BD had more negative lifestyle changes during the crisis than HC. Individuals with BD should be specifically supported during social distancing. Abstract: The COVID-19 pandemic affects both mentally healthy and ill individuals. Individuals with bipolar disorder (BD) constitute an especially vulnerable group. A multicentric online study was conducted in Austria, Denmark, and Germany after the first lockdown phase in 2020. In total, 117 healthy controls (HC) were matched according to age and sex to 117 individuals with BD. The survey included the Brief Symptom Inventory-18, Beck Depression Inventory-2, Pittsburgh Sleep Quality Index, and a self-constructed questionnaire assessing COVID-19 fears, emotional distress due to social distancing, lifestyle, and compliance to governmental measures. In individuals with BD, increased symptoms of depression, somatization, anxiety, distress due to social distancing, and poorer sleep quality were related to emotional distress due to social distancing. The correlation between emotional distress due to social distancing and anxiety showed 26% of shared variance in BD and 11% in HC. Negative lifestyle changes and lower compliance with COVID-19 regulatory measures were more likely to be observed in individuals with BD than in HC. These findings underscore the need for ongoing mental health support during the pandemic. Individuals with BD should be continuously supported during periods of social distancing to maintain a stable lifestyle and employ strategies to cope with COVID-19 fears.